Management of complex palatoradicular groove in maxillary lateral incisor - Singh, Ripu; Sharma, Shivalal; Goel, Khushboo (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Palatoradicular grooves are the developmental anomalies that owing to complexity in morphology and extent along the root length, can be an aetiology for periodontal destruction, endodontic involvement or both. We report a case of a 34 years male patient who presented with a chief complaint of pain and swelling in his upper left front region of jaw since one month. Clinical and radiographic examination confirmed presence of periodontal-endodontic lesion with respect to 22. Endodontic treatment followed by periodontal debridement, regenerative procedures, odontoplasty and sealing of the groove was done. Combined endodontic-periodontal approach was successful in resolving the pathology with satisfactory and stable healing seen clinically and radiographically for upto six months postoperative.